Price Deviation Supported by Arbitrage: Evidence from Family Business Groups - Kim, Woojin; Wang, Shu Feng (Asia-Pacific Journal of Financial Studies, 2019)
This paper examines how arbitrage may contribute to, rather than remove, temporary price deviation between two related securities. Based on a unique sample of stock-for-stock tender offers by a member firm for another member firm within Korean family business groups, we find that arbitrage opportunity exists in more than three quarters of the sample, which is consistent with Lamont and Thaler (2003). Outside investors’ tendering decisions and institutions’ short-selling are consistent with exploiting potential arbitrage opportunities, but not large enough to eliminate them. The prices of the two securities tend to diverge leading up to the tender offer, which may be impacted by the controlling families. This deviation, reflected in the exchange ratio of the two securities, is more likely to be sustained when there is more short-selling during the possible arbitrage period. Our results suggest that arbitrage may support temporary deviations in the relative prices of two related securities under certain circumstances.
Keywords: Business group; Korea; Limits to arbitrage; Mispricing